Revealing the relation between black hole growth and host-galaxy compactness among star-forming galaxies. Issue 4 (13th November 2020) - Ni, Q; Brandt, W N; Yang, G; Leja, J; Chen, C-T J; Luo, B; Matharu, J; Sun, M; Vito, F; Xue, Y Q; Zhang, K
ABSTRACT: Recent studies show that a universal relation between black hole (BH) growth and stellar mass ( M ⋆ ) or star formation rate (SFR) is an oversimplification of BH–galaxy coevolution, and that morphological and structural properties of host galaxies must also be considered. Particularly, a possible connection between BH growth and host-galaxy compactness was identified among star-forming (SF) galaxies. Utilizing ≈6300 massive galaxies with I 814W   <  24 at z < 1.2 in the Cosmic Evolution Survey (COSMOS) field, we perform systematic partial correlation analyses to investigate how sample-averaged BH accretion rate ($\rm \overline{BHAR}$ ) depends on host-galaxy compactness among SF galaxies, when controlling for morphology and M ⋆ (or SFR). The projected central surface mass density within 1 kpc, Σ1, is utilized to represent host-galaxy compactness in our study. We find that the $\rm \overline{BHAR}$ –Σ1 relation is stronger than either the $\rm \overline{BHAR}$ – M ⋆ or $\rm \overline{BHAR}$ –SFR relation among SF galaxies, and this $\rm \overline{BHAR}$ –Σ1 relation applies to both bulge-dominated galaxies and galaxies that are not dominated by bulges. This $\rm \overline{BHAR}$ –Σ1 relation among SF galaxies suggests a link between BH growth and the central gas density of host galaxies on the kpc scale, which may further imply a common origin of the gas in the vicinity of the BH and in the central ∼kpc of the galaxy. This $\rm \overline{BHAR}$ –Σ1 relation can also be interpreted as the relation between BH growth and the central velocity dispersion of host galaxies at a given gas content (i.e. gas mass fraction), indicating the role of the host-galaxy potential well in regulating accretion on to the BH.